Canva-Based MPI Analysis of Critical Thinking Skills for Class VI Elementary School Mathematics Story Problems - Marpaung, Dian Wahyu; Wiryanto; Tatag Yuli Eko Siswono (Jurnal Elementaria Edukasia, 2024)
This research was conducted because of students' inability to think critically, so there is a need for media interactive learning that can improve student learning outcomes, as well as teachers' ability to develop low IT-based learning media. This research aims to analyze the initial needs in developing Canva-based interactive media to improve the critical thinking skills of sixth grade elementary school students to solve Mathematics story problems on geometric material. It is hoped that Canva-based MPI can be a solution to students' difficulties in interpreting and solving story problems, which often require in-depth understanding and critical thinking skills. The method used in the research is Research and Development with the ADDIE research model, which consists: (1)Analysis, (2)Design, (3)Development, (4)Implementation, and (5)Evaluation. In addition, media validation was carried out by experts to evaluate the validity and effectiveness of Canva-based interactive media. The use of Canva results show that in developing learning media is able to provide more interesting and interactive story problem visualizations, thus having a positive impact on improving students' critical thinking abilities. It is hoped that this research can contribute to the development of effective and easily accessible learning media to improve the quality of mathematics learning in elementary schools, especially in terms skills to critical thinking solve story problems.